Digital capital : a bourdieusian perspective on the digital divide - Ragnedda, Massimo, 1976-; Ruiu, Maria Laura (Emerald points., 2020)
This work represents the first attempt to position digital capital as cumulative and transferable, independent from, and intertwined with the other five forms of capitals. The book aims to propose a theoretical toolkit and empirical model that can be used by policy makers to tackle social inequalities created by the digital exclusion of citizens.